The Relationship between the Structure and Thermal Properties of Bi2O3-ZnO-B2O3 Glass System - Sung-Hung Lan; Chin-Tung Lee; Yi-Sheng Lai; Chien-Chon Chen; Hsi-Wen Yang (Advances in Condensed Matter Physics)
The influence of Bi2O3 and melting temperature on the thermal and structural properties of xBi2O3-(60-x) ZnO-40B2O3 glasses has been investigated in this study. It is expected that these factors can be used to control the degree of reduction of Bi2O3, and the relationship between these factors and the color change of the process for bismuth glass is discussed. Due to high-temperature melting, the bismuth-doped borate glasses have changed into dark/black from original transparent yellow and the light transmittance will decrease, so it is not used in optical applications. The thermal properties of glass are measured by a thermomechanical analyzer (TMA), and the glass structure is analyzed by FTIR and XPS. The results show that the glass is mainly composed of [BiO6] octahedron, [BiO3] triangle, [BO4] tetrahedron, and triangle [BO3] units, and the network of the glass system is mainly bonded by B-O-B, B-O-Zn, B-O-Bi, and Bi-O-Bi. The glass thermal expansion coefficient (CTE) of this glass system increases with the increase of Bi2O3 content, and the O1s nuclear electron binding energy shifts to the lower energy direction with the increase of Bi2O3 addition. In terms of FTIR, as the melting temperature rises, the B-O-B bonding vibration concentration of [BO4] inside the borate glass decreases, and the density of B-O-B bonding vibration of [BO3] increases, Moreover, the increase in melting temperature increases the probability of reducing Bi ions to Bi0, reduces the bonding of Bi-O-B, and increases the bonding of B-O-B, and the CTE also slightly decreases.